2005
DOI: 10.1213/01.ane.0000184113.57416.dd
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Femoral Nerve Blockade or Epidural Analgesia After Total Knee Replacement: A Prospective Randomized Controlled Trial

Abstract: Because postoperative pain after total knee replacement (TKR) can be severe, we compared the analgesic efficacy of continuous femoral nerve blockade (CFNB) and continuous epidural analgesia (CEA) after TKR in this prospective randomized trial. Patients undergoing TKR under spinal anesthesia were randomized to receive either a femoral infusion of bupivacaine 0.2% (median infusion rate 9.3 mL/h) (n = 53) or an epidural infusion of ropivacaine 0.2% with fentanyl 4 microg/mL (median infusion rate 7.6 mL/h) (n = 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 6 publications
3
73
0
2
Order By: Relevance
“…Results: Group F used significantly less morphine compared with Group P (18.7 mg vs. 39.6 mg) during the first 48 hours after surgery (p<0.001). When compared with group P, the VRS scores both at rest and during movement were significantly lower in Group F at 4,8,12, 24, and 48 hours after TKA (for all comparisons p<0.001). In addition, patient satisfaction was better in Group F than Group P. Conclusion: This study suggests that a US-guided single-injection femoral nerve block following TKA improves patient satisfaction and reduces consumption of morphine during the first 48 hours.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Results: Group F used significantly less morphine compared with Group P (18.7 mg vs. 39.6 mg) during the first 48 hours after surgery (p<0.001). When compared with group P, the VRS scores both at rest and during movement were significantly lower in Group F at 4,8,12, 24, and 48 hours after TKA (for all comparisons p<0.001). In addition, patient satisfaction was better in Group F than Group P. Conclusion: This study suggests that a US-guided single-injection femoral nerve block following TKA improves patient satisfaction and reduces consumption of morphine during the first 48 hours.…”
mentioning
confidence: 73%
“…[8][9][10][11] In addition, femoral nerve blocks can reduce the reflex of the quadriceps muscle, thus reducing pain and muscle spasms, [12] which may provide a positive contribution in facilitating physical therapy and early ambulation, as well as reduce the length of hospitalization. [11,13] In this study, longer analgesia time may have resulted from the injection of high-volume LA tion, tourniquet time, duration of operation, and times from spinal injection to the FNB procedure between the two groups ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…With reference to previous studies, power calculations on the basis of a two-sided design at a significance level of 5 % (⍺ = 0.05) and a probability of 80 % (β = 0.20) revealed that at least 44 patients were needed to detect a 50 % reduction in pain scores (VAS ± SD = 3 ± 2.5) [7], and to compare the analgesic efficiency and the occurrence of adverse events it would require at least 66 participants [8].…”
Section: Methodsmentioning
confidence: 99%
“…However, over the past decade, the increased use of low molecular weight heparins and the proven rehabilitative benefits associated with continuous femoral nerve blocks have led to a renewed interest amongst anesthesiologists to perform regional anesthesia for the lower limb. [1][2][3][4] Despite this enthusiasm, there still persist many variances in clinical methods for lower extremity nerve blocks. Accordingly, a literature search of randomized clinical trials was undertaken to determine the best available approaches and techniques for regional anesthesia of the lower limb.…”
Section: Conclusion : Les Comptes Rendus Publiés D'erc Fournissent Dementioning
confidence: 99%